Short Term Performance Analysis of IPOs in India - Yadav, Naveen Ramesh; Dasgupta, Hirak; Moray, Rashmy (Asian Journal of Empirical Research, 2018)
The research is aimed at the short term IPO returns that are issued on the National Stock Exchange (NSE) and Bombay Stock Exchange (BSE). The evaluation of IPO is done on the basis of the returns generated on the day of issue, 10 and 30 days after the day of issue. The significance of this paper can be realized from the fact whether the return generated in short term in comparison to the market are more or less i.e. the IPO has outperformed the index as a benchmark. The study includes a sample of 28 IPO’s issued from the year 2013 to 2015. The results showed that the mean % performance of IPO on the day of issue, 10 and 30 days after the day of issue is 9%, 10% and 10% respectively for NSE and 8%, 9% and 14% respectively for BSE. The above results are also supported with relative valuation index which thus brings us to a very important conclusion that the Indian Stock market provides significant returns within 30 days from the date of issue of share.